Comparison of methods for selecting a promising walnut gene pool according to fruit quality - S. G. Biganova; Yu. I. Sukhorukikh; E. K. Pchikhachev (Труды по прикладной ботанике, генетике и селекции)
Background. Walnut (Juglans regia L.) is considered a particularly valuable plant for humans. A number of methods have been developed to select the species’ gene pool that produces high-quality fruits. Breeders need to know which of them ensures identification of the best ancestors. The objective of this work was to compare the effectiveness of the most frequently used techniques for selecting a valuable gene pool according to taste, extractability, weight, kernel yield, and overall fruit score. They were presented in the Program and Methods for Walnut Breeding (method 1) and the Program and Methodology of Variety Studies for Fruit, Berry and Nut Crops (method 2).Materials and methods. Statistical data processing was performed using the licensed Stadia-8 software.Results. Comparing the results with the program requirements for new cultivars, all the ancestors selected according to method 1 had better taste and higher kernel weight, while according to method 2 12.5% of the forms showed lower values. The recommended kernel yield of 50% or more turned out to be lower than the threshold value in 14.29% (method 1) and 62.5% (method 2) of the selected ramets. Evaluation by to method 1 showed that the group of the “superior quality” breeding category had higher average values in taste (by 3.63%), weight (7.86%), extractability (4.25%), and kernel yield (9.9%). When selecting the first-rank forms by method 1, the values were higher in extractability (by 0.25%), weight (5.26%), taste (3.09%), kernel yield (7.55%), and overall score (7.61%). In the average values for the first-rank and second-rank forms, the excess was by 4.44, 21.91, 4.75, 9.67, and 9.86%, respectively.Conclusions. When selecting a promising walnut gene pool, method 1 provides for stricter selection and higher food quality indicators (taste, extractability, weight, kernel yield, and overall fruit score) compared to method 2.